Implementasi Kebijakan New Normal pada Pelaku Usaha Waterpark Transera di Kabupaten Bekasi - Iwan Bara Budiman; Sari Ningsih (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2022)
The purpose of this study was to conclude that the management of the waterpark Bekasi supported it completely and ignored the agnation of new normal policies, Management understands the importance of applying health protocols to businesses and individuals so that the waterpark begins implementing strict, intensive health protocols starting with all of waterpark Bekasi, as well as the transfer of tools and the resulting infrastructure of the covid-19 pandemic. Causing various policies to break the spread of the covid-19 virus in Indonesia. Efforts by governments are among those that are implemented Civility to society in order to carry out Covid-19, excluding activities in all forms of crowds, assemblies, and avoiding meetings involving many people. Such efforts are aimed at communities that can be done to break the current covid-19 pandemic chain. The provisions of infrastructure in accordance with government regulations and therefore Transera waterpark provide comfort and security to the organizers.